Effects of dietary of Bacillus coagulans, whey powder, and their interaction on the performance of Lohmann LSL-lite laying hens in the late production phase - Zahra Hamzehee; Mehran Torki; Khodabakhsh Rashidi; Alireza Abdolmohammadi (PLoS ONE, 2025)
Due to the need to produce high-quality and healthy eggs, the current experiment was conducted to investigate the impact of dietary supplementation of whey powder (WP), Bacillus coagulans (B. coagulans), and their combination (MIX) on the production performance, egg quality, blood biochemical parameters, and histomorphological parameters of Lohmann LSL-lite laying hens. 144 Lohmann laying hen (75 weeks) were randomly assigned to 4 different dietary treatments, with 6 replications and 6 hens per cage. The hens were fed a basal diet (control, CON), the basal diet supplemented with 1 g/kg WP, 1 g/kg B. coagulans (4 × 106 CFU), and 1 g/kg WP plus 1 g/kg B. coagulans probiotic for 12 weeks. Feed intake and egg weight were not affected by the treatments at any stage of the trial (P > 0.05). No significant interaction was found between WP and B. coagulans in egg quality parameters and blood-biochemical parameters other than malondialdehyde (P < 0.05). The level of malondialdehyde in serum was reduced when WP was used along with B. coagulans compared to when WP was used alone. However, egg production in all periods and egg mass in the first period were affected by the synergistic effect of WP and B. coagulans. Furthermore, FCR was reduced in the first period (75–80 weeks) under the influence of the MIX group compared to the control group or when used alone (P < 0.05). The color of the yolk was increased in the group receiving B. coagulans compared to the control group (P < 0.05). Therefore, in birds fed with B. coagulans, a significant increase in the width of the villi in the ileum was observed (P ≤ 0.05). Interestingly, B. coagulans and WP reduced performance when used alone compared to the control, but improved performance when combined. In conclusion, the simultaneous use of WP and B. coagulans in diet can probably improve the parameters of production performance, FCR, and serum malondialdehyde level at the end of the production period of Lohmann laying hens.